A Study on Impact of Credit Risk Management on the Profitability of Indian Banks - Butola, Punyata; Dube, Praveen; Jain, Vijay Kumar (International Journal of Management and Sustainability, 2022)
The main aim of this study is to find a statistical association between credit risk management (CRM) and profitability within Indian banks. Secondary data from 38 Indian scheduled commercial banks was collected, for the time period from 2005-2019 and examined using a panel data regression. For the purpose of this study, return on assets (ROA) is considered a dependent variable and an indicator of profitability, while the credit to deposit ratio (CDR), net interest margin (NIM), operating profits to total assets (OPA), capital adequacy ratio (CAR), provision coverage ratio (PCR) and net non- performing assets to net advances (NNPA) are considered the determinants of CRM and classified as independent variables. The statistical finding indicates that the CDR, OPA and CAR are all positively related to the profit rate (ROA) while NIM, NNPA and PCR all found to be negatively related to the profit rate (ROA) and statistically show a significant association except PCR.